PKM2-mediated metabolic reprogramming of microglia in neuroinflammation - Qi Zhang; Sha-Sha Wang; Zhao Zhang; Shi-Feng Chu (Cell Death Discovery)
Abstract Microglia, the resident immune cells of the central nervous system, undergo metabolic reprogramming during neuroinflammation, playing a crucial role in the pathogenesis of neurological disorders such as Parkinson’s disease. This review focuses on Pyruvate Kinase M2 (PKM2), a key glycolytic enzyme, and its impact on microglial metabolic reprogramming and subsequent neuroinflammation. We explore the regulatory mechanisms governing PKM2 activity, its influence on microglial activation and immune responses, and its contribution to the progression of various neurological diseases. Finally, we highlight the therapeutic potential of targeting PKM2 as a novel strategy for treating neuroinflammation-driven neurological disorders. This review provides insights into the molecular mechanisms of PKM2 in neuroinflammation, aiming to inform the development of future therapeutic interventions.